Psychiatric comorbidity in alcohol use disorders: results from the German S3 guidelines - Preuss, Ulrich W.; Mann, Karl (European archives of psychiatry and clinical neuroscience, 2018)
Alcohol use disorders (AUD) have a high comorbidity with mental disorders. Vice versa, alcohol consumption plays an important role in affective disorders, anxiety disorders, ADHD, schizophrenic psychosis, and other mental disorders. In developing the current interdisciplinary, evidence-based treatment guideline on screening, diagnostics, and treatment of AUD, available research on comorbid mental diseases in AUD has been compiled to generate recommendations for treatment. The guideline was prepared under the responsibility of the German Association for Psychiatry, Psychotherapy, and Psychosomatics (DGPPN) and the German Association for Addiction Research and Therapy (DG-Sucht). To meet the methodological criteria for the highest quality guidelines (“S3-criteria”) as defined by the Association of Scientific Medical Societies in Germany (AWMF), the following criteria were employed: (1) a systematic search, selection, and appraisal of the international literature; (2) a structured process to reach consensus; and (3) inclusion of all relevant representatives of future guideline users. After assessing and grading the available literature, the expert groups generated several recommendations for the screening, diagnosis, and treatment of comorbid mental disorders. These recommendations were subdivided into psycho-, pharmaco-, and combination therapies. These are the first guidelines ever to make specific treatment recommendations for comorbid mental diseases in AUD. The recommendations extend to different treatment approaches including diagnostics and settings to present available effective and state-of-the-art treatment approaches to clinicians. Hitherto, many clinical constellations have not been addressed in research. Therefore, recommendations for future research are specified.
Published online: 24 April 2017
Gesehen am 25.09.2018